Logic and contemporary rhetoric : - Kahane, Howard (Wadsworth Thomson Learning, 2001)
This leading text introduces students to good reasoning using a wealth of current, relevant, and stimulating examples all put together in Howard Kahane's uniquely witty and invigorating writing style that makes this the book of choice for keeping students interested. Combined with examples from TV, newspapers, magazines, advertisements, and of course, our political institutions, the text not only brings the concepts alive for students, but puts the skills into a context that students will retain and use throughout their lives. A book you can count on students to read